Medicinal Plants: Guests and Hosts in the Heterologous Expression of High-Value Products - Vasilev, Nikolay (Planta Medica, 2021)
Medicinal plants play an important dual role in the context of the heterologous expression of high-value pharmaceutical products. On the one hand, the classical biochemical and modern omics approaches allowed for the discovery of various genes encoding biosynthetic pathways in medicinal plants. Recombinant DNA technology enabled introducing these genes and regulatory elements into host organisms and enhancing the heterologous production of the corresponding secondary metabolites. On the other hand, the transient expression of foreign DNA in plants facilitated the production of numerous proteins of pharmaceutical importance. This review summarizes several success stories of the engineering of plant metabolic pathways in heterologous hosts. Likewise, a few examples of recombinant protein expression in plants for therapeutic purposes are also highlighted. Therefore, the importance of medicinal plants has grown immensely as sources for valuable products of low and high molecular weight. The next step ahead for bioengineering is to achieve more success stories of industrial-scale production of secondary plant metabolites in microbial systems and to fully exploit plant cell factoriesʼ commercial potential for recombinant proteins.
Keywords: recombinant DNA technology; secondary plant metabolites; therapeutic proteins; heterologous expression; metabolic engineering; synthetic biology